Voices in the air poems for listeners - Nye, Naomi Shihab 1952- (Greenwillow Books, an Imprint of HarperCollins Publishers, 2018)
"Ninety-five poems pay tribute to essential voices past and present that have the power to provoke us, lead us, and give us hope" ...
Includes bibliographical references and indexes
Keywords: Inspiration -- Juvenile poetry; Hope -- Juvenile poetry; Jugendlyrik; Hoffnung; Amerikanisches Englisch; Jugendbuch; Anthologie